Fabrication and characterizations of nanocomposite flexible films of ZnO and polyvinyl chloride/poly(N-vinyl carbazole) polymers for dielectric capacitors - A.A. Al-Muntaser; Essam Banoqitah; M.A. Morsi; Aysh Y. Madkhli; J.A. Mohammed Abdulwahed; Reem Alwafi; Abdullah F. Al Naim; Abdu Saeed (Arabian Journal of Chemistry, 2023)
Polymer-based energy storage has recently attracted the attention of researchers. Herein, via the sol–gel method, we prepared zinc oxide nanoparticles (ZnO NPs), as nanofiller up to 5 wt% filling levels, and a host polymeric blend matrix of polyvinyl chloride (PVC) and poly (N-vinyl carbazole) (PVK) were taken to synthesize nanocomposite films via the solution casting. The ratio of PVC: PVK was 90:10 wt%. The X-ray diffraction (XRD) results indicated that the prepared nanocomposite films’ crystallinity decreased as ZnO NPs content increased; it decreased from 54.23 to 22.14 %. The scanning electron microscope (SEM) micrographs revealed good miscibility of the prepared PVC/PVK blend and the homogeneous distribution of ZnO NPs within the host blend matrix. The thermal stability of the prepared nanocomposites was studied through the TGA technique, and the thermal activation energy was calculated using the Coats-Redfern method. In the optical results, the optical absorption spectra revealed that the energy gap for the allowed direct transition reduced under adding ZnO NPs; it reduced from 3.61 eV for the pure PVC/PVK blend to 2.96 eV for the nanocomposite film with ZnO nanofiller content of 5 wt%. AC conductivity experiments revealed that the electrical/dielectric properties of the nanocomposite films get enhanced by increasing the ZnO NPs content. Following the incorporation of the ZnO NPs, the AC electrical conductivity (σac), dc electrical conductivity (σdc), dielectric constant (ε′), and dielectric loss (ε″) values of PVC/PVK/ZnO nanocomposite films get improved; the σdc values increased from 6.46 × 10−16 S/cm for the blend PVC/PVK matrix to 3.63 × 10−13 S/cm for nanocomposites with ZnO NPs content of 5 wt%. Additionally, both ε′ and ε″ values increased while increasing the ZnO NPs content. These findings could suggest that the prepared PVC/PVK/ZnO nanocomposite films could be a promise for the applications of dielectric energy storage polymer-based capacitors.